Adipophilin/perilipin‐2 as a lipid droplet‐specific marker for metabolically active cells and diseases associated with metabolic dysregulation. Issue 4 (24th January 2013) - Straub, Beate Katharina; Gyoengyoesi, Benedek; Koenig, Maria; Hashani, Merita; Pawella, Lena Maria; Herpel, Esther; Mueller, Wolf; Macher‐Goeppinger, Stephan; Heid, Hans; Schirmacher, Peter
<x xml:space="preserve">Abstract</x> Aims Lipid droplets (LDs) are dynamic storage compartments for energy‐rich fats that are nearly ubiquitously present in eukaryotic cells, exerting tissue‐specific functions in metabolically active cell types, and are increased in conditions following cellular damage or lipid overload. The LD–cytoplasm interface is stabilized by amphiphilic proteins of the PAT/perilipin family (perilipin/perilipin‐1, adipophilin/perilipin‐2, and TIP47/perilipin‐3). We evaluated the value of adipophilin immunohistochemistry for the diagnosis of diseases associated with LD accumulation. Methods and results In human tissues, adipophilin‐positive LDs were especially prominent in steroidogenic cells of the adrenal gland, testis, and ovary, in hepatocytes and hepatic stellate cells, in cardiac, striated and smooth myocytes, in lactating mammary gland epithelial cells, and in plurivacuolar adipocytes. Variable amounts of adipophilin‐positive LDs were also detected almost ubiquitously in epithelial cells of the gastrointestinal tract and skin. In diseases associated with lipid storage, adipophilin was strongly expressed in lipid‐laden macrophages in atherosclerosis, in cardiomyopathies, kidney diseases, hepatocyte steatosis, colon ischaemia, and at the border of organ infarcts. Conclusions Adipophilin immunohistochemistry visualizes small LDs in tissues under physiological and disease conditions that are not visible by conventional light microscopy. Immunohistology for adipophilin may facilitate histomorphological diagnosis of diseases and definition of the extent of metabolic dysregulation, such as in organ infarcts, cardiomyopathies, kidney diseases, and microvesicular steatosis.